Labor market distortions in major emerging-market economies: Some CGE estimates - Liboreiro, Pablo R. (Universitas Islam Indonesia, 2023)
Purpose ― In the present study, the effects of labor market distortions on economic structure and efficiency are estimated for seven emerging-market countries: Brazil, China, Indonesia, India, Mexico, Russia, and Turkey. Methods ― The estimates are based on a computable equilibrium (CGE) model that allows simulation of the inter-industry links of 56 industries plus a sector representing the rest of the world from data collected in the World Input-Output Database (Release 2016) for the period 2000-2014. Findings ― The results show that wage differentials appear to be distortionary, especially in the cases of countries with high wage-income inequality. Moreover, it seems that labor market distortions in emerging-market countries are subject to the rural-urban dichotomy and urban labor-market imperfections. Finally, the results show that the removal of wage differentials affects the terms of trade, which are improved in most but not all cases.Implication ― The conclusions of the present study have policy implications. In countries where the rural-urban dichotomy is the main distortion in labor markets, increasing urbanization can stimulate efficiency; when this is not the case, further reform of urban labor markets is needed. However, it cannot be ruled out in advance that a policy aimed at enhancing labor mobility may have a negative impact on the terms of trade. Originality ― The estimation method used in the present study presents certain advances over others found in the literature, as it becomes possible to estimate the effects of labor-market distortions while considering the interdependencies between different sectors, as well as to plausibly estimate the effects on trade. The present study also uses a large quantity of data, which is expected to add robustness to the study’s conclusion.